2006
DOI: 10.1007/s10517-006-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the vitamin status in nursing women by vitamin content in breast milk

Abstract: The dependence of daily vitamin excretion with breast milk on dietary vitamin content and blood vitamin level was studied in nursing women. Breast mils vitamins were assayed in women supplied with vitamins. We identified the criteria for adequate vitamin supply in nursing women over the 1st month after labor (vitamins A, 130 microg; vitamin B1, 100 microg; vitamin B2, 130 microg; vitamin E, 750 microg; vitamin B6, 60 microg).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 3 publications
1
30
0
1
Order By: Relevance
“…In transition milk, the values found in different populations were also similar, with the exception of one study conducted in Russia, 10 which presented lower mean values, as well as the study by Quiles et al, 8 whose values were higher than others. Kodentsova and Vrzhesinskaya, 10 however, used samples of women who were between the third and tenth days of lactation together with others, who were between the 14 th and 20 th days, which may have influenced the results.…”
Section: Lactation Stagesupporting
confidence: 71%
See 3 more Smart Citations
“…In transition milk, the values found in different populations were also similar, with the exception of one study conducted in Russia, 10 which presented lower mean values, as well as the study by Quiles et al, 8 whose values were higher than others. Kodentsova and Vrzhesinskaya, 10 however, used samples of women who were between the third and tenth days of lactation together with others, who were between the 14 th and 20 th days, which may have influenced the results.…”
Section: Lactation Stagesupporting
confidence: 71%
“…10 However, a study in Canada observed a positive correlation between vitamin E found in milk and multivitamin supplementation, as reported by survey participants. 36 Dimenstein et al, 29 when analyzing tocopherol in the milk of 30 adult women in Northeastern Brazil, observed that supplementation with a capsule containing synthetic vitamin E (49.4 mg dl-alpha-tocopherol) did not lead to an increase in the concentration of the vitamin in colostrum 24 hours after supplementation.…”
Section: Maternal Habitual Dietary Intake and Vitamin E Supplementationmentioning
confidence: 87%
See 2 more Smart Citations
“…Most of the researches on B-vitamins have been limited to Caucasian [11,[15][16][17][19][20][21][22][23], East Asian (i.e. Japanese and Korean) [4,24,25], and Africa populations [26][27][28] with little data from Southeast Asian [18] and American populations [29,30].…”
Section: Introductionmentioning
confidence: 99%